Electrode material and electrode using same

By using a titanium suboxide support with a high specific surface area and noble metals, the electrode material achieves enhanced resistance to oxidation and high conductivity, addressing the limitations of conventional materials in fuel cells.

JP7647545B2Active Publication Date: 2025-03-18SAKAI CHEM IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021501869
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-26
Filing Date
2020-02-07
Publication Date
2025-03-18
Estimated Expiration
2040-02-07

AI Technical Summary

Technical Problem

Conventional electrode materials for fuel cells, such as Pt-supported carbon and Ti4O7, suffer from oxidation during the electrode-forming process, leading to reduced performance and durability, especially at high potentials.

Method used

A titanium suboxide support with a specific surface area of at least 5m^2/g, carrying Pt and/or its oxides, and at least one noble metal selected from Ir, Ru, Rh, and Pd, is used to create an electrode material that is resistant to oxidation and maintains high conductivity.

Benefits of technology

The resulting electrode material exhibits excellent resistance to high potentials and high conductivity, leading to improved durability and performance in fuel cells and other electrochemical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647545000003
    Figure 0007647545000003
  • Figure 0007647545000004
    Figure 0007647545000004
  • Figure 0007647545000005
    Figure 0007647545000005
Patent Text Reader

Abstract

The present invention provides an electrode material capable of forming an electrode having excellent resistance to high potential and high conductivity, and an electrode and a fuel cell using the same. The present invention relates to a titanium suboxide support on which Pt and / or its oxide, and at least one noble metal selected from Ir, Ru, Rh, and Pd and / or its oxide are supported, and which has a BET specific surface area of ​​5 m 2 / g or more, 20m 2 / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode material and an electrode using the same, and more particularly to an electrode material suitable as an electrode material for a fuel cell and an electrode using the same. [Background technology]

[0002] Fuel cells are devices that generate electricity by electrochemically reacting fuels such as hydrogen or alcohol with oxygen, and are classified into polymer electrolyte fuel cells (PEFCs), phosphoric acid fuel cells (PAFCs), molten carbonate fuel cells (MCFCs), solid oxide fuel cells (SOFCs), etc., depending on the electrolyte and operating temperature. For example, polymer electrolyte fuel cells are used in stationary power sources and fuel cell vehicles, and are required to maintain the desired power generation performance over a long period of time.

[0003] Of these fuel cells, polymer electrolyte fuel cells (PEFCs) use a polymer membrane (ion exchange membrane) with ion conductivity as the electrolyte, and generally use an electrode material in which platinum (Pt) is supported on carbon, a conductive material. In PEFCs, hydrogen supply shortages can occur due to water clogging of the fuel flow path or water freezing, and when this occurs, the anode potential rises sharply and the cell polarity is reversed, resulting in a polarity reversal state. In an anode in a polarity reversal state, instead of the reaction in which hydrogen is oxidized, reactions in which water is decomposed and carbon is oxidized (corroded) supply protons, so the potential instantly exceeds 1.5V vs RHE, and carbon oxidation (C+2H2O→CO2+4H++4e - ), which causes a significant decrease in battery performance. In order to avoid such a decrease in battery performance, a method has been proposed in which Pt is supported on a conductive oxide Ti4O7, which is not oxidized and lost, instead of carbon as a support (see Patent Document 1), and a method has been proposed in which iridium is added or supported as a water electrolysis (oxygen generation) catalyst to suppress the rise in anode potential (see Non-Patent Document 1). In addition, a method has been proposed in which Pt and Ir are supported on a support mainly made of a conductive oxide Ti4O7 (Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 096815 [Patent Document 2] DE 202015106071 A1 [Patent Document 3] Korean Patent Publication No. 2018-0017861 [Non-patent literature]

[0005] [Non-Patent Document 1] 59th Battery Symposium Proceedings 1H23 (Published November 27, 2018) Summary of the Invention [Problem to be solved by the invention]

[0006] The Pt-supported Ti4O7 described in the above-mentioned Patent Document 1 has higher durability when exposed to a high potential than the conventionally used Pt-supported carbon. However, although the electrical conductivity of the Pt-supported Ti4O7 in powder form is equivalent to that of the Pt-supported carbon, the powder is oxidized when the powder is mixed with a resin and a solvent and dispersed in the process of making an electrode, which leads to a decrease in the performance of the electrode. Therefore, the inventors' investigations have revealed that there is room for improving the oxidation resistance of the powder. Furthermore, as described in Non-Patent Document 1, when iridium is added or supported, it is possible to temporarily suppress the oxidation of carbon, but if an abnormally high potential state continues for a certain period of time, it is not possible to avoid the decrease in power generation performance due to the oxidation of carbon, and the effect is insufficient. Furthermore, the Ti4O7 support shown in Patent Document 2 has a particle diameter of about 50 nm (converted to a specific surface area of ​​30 m 2 / g), the effect of grain boundary resistance between particles becomes large, and the electrical conductivity is reduced to 1×10 -3 S / m (converted to volume resistivity of 1×10 1The specific surface area of ​​the Ti4O7 support is small, and the electrical conductivity is insufficient for use as an electrode material. On the other hand, when the specific surface area of ​​the Ti4O7 support is small, a uniform electrode cannot be obtained during electrode formation, and noble metals such as Pt cannot be supported uniformly, so sufficient power generation performance cannot be achieved. Furthermore, the support shown in Patent Document 3, while mainly composed of Ti4O7, also contains cobalt element and Ti5O9, which is a higher order titanium suboxide than Ti4O7, and these may not contribute much to the performance as an electrode material, and therefore the performance as an electrode is considered to be insufficient. As described above, all of the conventional materials have room for improvement in terms of their performance as electrode materials.

[0007] In view of the above-mentioned current situation, an object of the present invention is to provide an electrode material capable of forming an electrode having excellent resistance to high potential and high conductivity, and an electrode and a fuel cell using the same. [Means for solving the problem]

[0008] The present inventors have investigated a material that has excellent resistance to high potentials and has high conductivity even when used as an electrode, and have discovered a material that has Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide supported on a titanium suboxide support on which no peaks other than those due to Ti4O7 and / or Ti3O5 are observed in powder X-ray diffraction, and that has a BET specific surface area of ​​5 m 2 / g or more, 20m 2 The present inventors have found that, when a material having a molecular weight of 0.1 to 1.0 μg / g or less is used as an electrode material, oxidation is suppressed even when a resin and a solvent are mixed and dispersed in the electrode formation process, and therefore an electrode having excellent resistance to high potential and high conductivity can be obtained, which has led to the completion of the present invention.

[0009] That is, the present invention provides a titanium suboxide support having a structure in which Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide are supported on the titanium suboxide support, which does not show any peaks other than those derived from Ti4O7 and / or Ti3O5 in powder X-ray diffraction, and has a BET specific surface area of ​​5 m 2 / g or more, 20m 2 / g or less.

[0010] The Pt and / or its oxide, and at least one noble metal selected from Ir, Ru, Rh and Pd and / or its oxide preferably have an average primary particle size of 1 to 20 nm.

[0011] The at least one noble metal selected from Ir, Ru, Rh and Pd is preferably Ir and / or Ru.

[0012] The electrode material is preferably an electrode material for a polymer electrolyte fuel cell.

[0013] The present invention is also an electrode constructed from the electrode material of the present invention.

[0014] The present invention also relates to a fuel cell comprising the electrode of the present invention.

[0015] The present invention also relates to a water electrolysis cell comprising the electrode material of the present invention. Effect of the Invention

[0016] The electrode material of the present invention is a material capable of forming an electrode that can sufficiently withstand a high potential and has high conductivity. Therefore, it is extremely useful as a conductive material used for electrodes of fuel cells such as polymer electrolyte fuel cells, water electrolysis cells, solar cells, transistors, display devices such as liquid crystal, etc., as well as antistatic materials, heat ray shielding materials, etc. Among them, it is particularly useful as an electrode material for polymer electrolyte fuel cells. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows the results of powder X-ray diffraction measurements of the titanium suboxide supports used in Example 1 and Comparative Examples 1 to 4. [Diagram 2] FIG. 1 shows the results of powder X-ray diffraction measurements of the titanium suboxide supports used in Examples 2, 4, 5, and 6. [Diagram 3] FIG. 1 shows the results of powder X-ray diffraction measurement of the titanium suboxide support used in Example 3. [Figure 4] FIG. 2 is an electron microscope photograph of the powder obtained in Example 1. [Diagram 5] FIG. 2 is an electron microscope photograph of the powder obtained in Example 2. [Figure 6] FIG. 2 is an electron microscope photograph of the powder obtained in Example 3. [Figure 7] FIG. 1 is an electron microscope photograph of the powder obtained in Example 4. [Figure 8] FIG. 1 is an electron microscope photograph of the powder obtained in Example 5. [Figure 9] FIG. 1 is an electron microscope photograph of the powder obtained in Example 6. [Figure 10] FIG. 2 is an electron microscope photograph of the powder obtained in Comparative Example 1. [Figure 11] FIG. 2 is an electron microscope photograph of the powder obtained in Comparative Example 2. [Figure 12] FIG. 1 is an electron microscope photograph of the powder obtained in Comparative Example 4. [Figure 13] FIG. 1 is an electron microscope photograph of the powder obtained in Comparative Example 6. [Figure 14] FIG. 2 is a diagram showing the results of X-ray diffraction measurement of the powder obtained in Example 1. [Figure 15] FIG. 2 is a diagram showing the results of powder X-ray diffraction measurement of the powder obtained in Example 2. [Figure 16] FIG. 1 shows the results of powder X-ray diffraction measurement of the powder obtained in Example 3. [Figure 17] FIG. 1 shows the results of powder X-ray diffraction measurement of the powder obtained in Example 4. [Figure 18] FIG. 1 shows the results of powder X-ray diffraction measurement of the powder obtained in Example 5. [Figure 19] FIG. 1 shows the results of powder X-ray diffraction measurement of the powder obtained in Example 6. [Figure 20]FIG. 2 is a diagram showing the results of powder X-ray diffraction measurement of the powder obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] A preferred embodiment of the present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified and applied as appropriate within the scope that does not change the gist of the present invention.

[0019] 1. Electrode material The electrode material of the present invention has a structure in which Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide are supported on a titanium suboxide support in which no peaks other than those derived from Ti4O7 and / or Ti3O5 are observed in powder X-ray diffraction, and has a BET specific surface area of ​​5 m 2 / g or more, 20m 2 / g or less. By supporting a precious metal, the specific surface area of ​​the electrode material becomes larger than the BET specific surface area of ​​the titanium suboxide support.

[0020] The titanium suboxide support preferably has a crystal phase of single Ti4O7 phase, single Ti3O5 phase, or a mixed phase of Ti4O7 and Ti3O5. In the present specification, the term "titanium suboxide support in which no peaks other than those due to Ti4O7 and / or Ti3O5 are observed in powder X-ray diffraction" refers to an electrode material in which Ti4O7 and / or Ti3O5 are present and no other titanium oxides are present in the X-ray diffraction (XRD) measurement pattern measured in a state in which Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide are supported. The other titanium oxides include anatase-type, brookite-type, or rutile-type titanium oxide, Ti n O 2n-1(n is an integer of 2 or 5 to 9), and TiO. Generally, titanium oxides have different peak positions in their X-ray diffraction measurement patterns depending on their structures, and this can be used to determine whether Ti4O7 and / or Ti3O5 are present and whether other titanium oxides are not present. In the present invention, the determination is made by the following method. If the XRD measurement data contains a lot of noise overall, the following judgments may be made after smoothing and removing background using analysis software provided with the XRD (e.g., the powder X-ray diffraction pattern comprehensive analysis software JADE7J provided with the Rigaku X-ray diffractometer (RINT-TTR3)).

[0021] <ti4o7> If peaks are present in the pattern at 2θ=26.0 to 26.6° and 2θ=20.4 to 21.0°, it is determined that Ti4O7 is present. <ti3o5> If peaks are present in the pattern at 2θ=26.0 to 26.6° and 2θ=18.6 to 19.2°, it is determined that Ti3O5 is present.

[0022] <Ti n O 2n-1 (n represents an integer of 5 to 9), and rutile-type titanium oxide> In the pattern, if the ratio of the intensity of the maximum peak present at 2θ=26.0-26.6° to the intensity of 100 and the intensity of the maximum peak at 2θ=27.6-27.7° is 15 or less, it cannot be distinguished from other titanium oxide peaks and noise. n O 2n-1 (n represents an integer of 5 to 9), and it is determined that rutile-type titanium oxide is not present.

[0023] <Anatase and brookite titanium dioxide> In the pattern, if the ratio of the intensity of the maximum peak present at 2θ=26.0 to 26.6°, which is 100, to the intensity of the maximum peak present at 2θ=25.0 to 25.6° is 15 or less, it is indistinguishable from peaks of other titanium oxides and noise, and it is determined that anatase-type and brookite-type titanium oxide are not present.

[0024] <ti2o3> In the pattern, if the ratio of the intensity of the maximum peak present at 2θ=26.0 to 26.6° is 15 or less to the intensity of the maximum peak present at 2θ=23.5 to 24.1°, which is 100, it is determined that Ti2O3 is not present because it cannot be distinguished from peaks of other titanium oxides and noise.

[0025] <tio> In the pattern, the peaks assigned to TiO overlap with the peaks of Ti4O7 or Ti3O5, but the peak intensity at 2θ=62.1 to 62.7° is lower than that of Ti4O7 or Ti3O5. Therefore, if the ratio of the intensity of the maximum peak present at 2θ=62.1 to 62.7° to the intensity of the maximum peak present at 2θ=26.0 to 26.6° (100) is 30 or less, it is determined that TiO is not present.

[0026] The electrode material of the present invention has a BET specific surface area of ​​5 m 2 / g or more, 20m 2 / g or less. Such a specific surface area increases the catalytic activity of the electrode material, resulting in excellent electrode performance. The BET specific surface area is preferably 7 m 2 / g or more, more preferably 9m 2 / g or more. 5m 2 If the BET specific surface area is less than 20 m / g, the catalytic activity will be low and the electrode performance may be insufficient. 2 If the specific surface area is greater than 15 m / g, the contact resistance between the support particles increases. 2 / g or less. The BET specific surface area of ​​the electrode material can be measured by the method described in the Examples below.

[0027] The amount of Pt and / or its oxide supported in the electrode material of the present invention is preferably 1 to 50% by weight. With such a supported amount, the electrode material has better electrode performance. The supported amount is more preferably 2 to 30% by weight, and further preferably 4 to 20% by weight.

[0028] The amount of at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide supported in the electrode material of the present invention is preferably 1 to 50% by weight. Such a supported amount makes the electrode material have better electrode performance. The supported amount is more preferably 2 to 30% by weight, and further preferably 6 to 20% by weight.

[0029] In the electrode material of the present invention, it is necessary that at least one kind of precious metal selected from Ir, Ru, Rh, and Pd and / or an oxide thereof and the above-mentioned Pt and / or an oxide thereof are supported on the same support, and sufficient effects cannot be obtained even if a support supporting at least one kind of precious metal selected from Ir, Ru, Rh, and Pd and / or an oxide thereof is physically mixed with a support supporting the above-mentioned Pt and / or an oxide thereof.

[0030] In the electrode material of the present invention, the weight ratio of the amount of at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide to the amount of Pt and / or its oxide is preferably 0.1 to 10. With such a ratio, the electrode material has better electrode performance. The weight ratio is more preferably 0.5 to 5.0, and further preferably 0.8 to 3.0.

[0031] The above-mentioned Pt and / or its oxide, and at least one kind of precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide preferably have an average primary particle size of 1 to 20 nm. When the average primary particle size is within this range, the electrode material has better electrode performance. The average primary particle size is more preferably 2 to 15 nm, and further preferably 3 to 10 nm. The average primary particle size of Pt and / or its oxide, and at least one kind of noble metal selected from Ir, Ru, Rh and Pd and / or its oxide can be measured by the method described in the examples below.

[0032] The average primary particle size of the Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh and Pd and / or its oxide is preferably 70% or less, and more preferably 30% or less, of the average primary particle size of the titanium suboxide support.

[0033] The at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide supported on the titanium suboxide support may be any of these precious metals and / or their oxides, but the precious metal is preferably Ir and / or Ru. By supporting Ir and / or Ru or their oxides, the catalytic activity of the obtained electrode material is increased, and the electrode material has better electrode performance.

[0034] The above-mentioned Pt and at least one precious metal selected from Ir, Ru, Rh and Pd form an alloy depending on the production conditions described below. Since this may further improve the electrical conductivity and electrochemical properties, a part or the whole of the above-mentioned precious metal particles may be alloyed with titanium constituting the support.

[0035] The electrode material of the present invention is a titanium suboxide support having Pt and / or an oxide thereof, and at least one precious metal selected from Ir, Ru, Rh and Pd and / or an oxide thereof supported thereon, and may also have other metal species supported thereon as long as the electrode performance is not adversely affected.

[0036] 2. Manufacturing method of electrode material The electrode material of the present invention can be produced by a production method including: a step (1) of obtaining a titanium suboxide support showing no peaks other than those derived from Ti4O7 and / or Ti3O5 in powder X-ray diffraction; and a step (2) of supporting Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh and Pd and / or its oxide on the titanium suboxide support obtained in step (1). Steps (1) and (2) will be described below in order.

[0037] 1) Process (1) Step (1) is not particularly limited as long as it is a step that can provide the above-mentioned titanium suboxide support, but is preferably a step of calcining a raw material mixture containing titanium oxide and / or titanium hydroxide under a reducing atmosphere. When titanium oxide or titanium hydroxide is used, impurities contained during the production of the electrode material are reduced, and since these are easily available, they are excellent in terms of stable supply. Among them, it is preferable to use rutile titanium oxide. This makes it possible to obtain a titanium suboxide support that shows no peaks other than those derived from Ti4O7 and / or Ti3O5 in powder X-ray diffraction, and that supports Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide, and has a BET specific surface area of ​​5 m. 2 / g or more, 20m 2 More preferably, the titanium oxide has a specific surface area of ​​20 m 2 / g or more, thereby more efficiently obtaining a titanium suboxide support having a large specific surface area and a single Ti4O7 crystalline phase. 2 The advantage of this method is that it uses rutile-type titanium dioxide with a solubility of 1 / g or more.

[0038] A reduction assistant may be added to the raw material mixture. Examples of the reduction assistant include titanium metal, titanium hydride, sodium borohydride, etc., and any of these can be used. The amount of the reducing agent added is preferably 0.05 to 0.5 by weight relative to titanium oxide and / or titanium hydroxide (the total amount when two or more kinds are used), and more preferably 0.1 to 0.4.

[0039] The raw material mixture can be obtained by mixing the above-mentioned components by a normal mixing method, but in this case, it is preferable to adopt a dry method. That is, the raw material mixture is preferably a dry mixture. This makes it possible to more efficiently obtain the titanium suboxide support represented by the above composition formula. The raw material mixture is particularly preferably a dry mixture containing rutile titanium oxide and metallic titanium or titanium hydride. Each raw material may be used in one or more types.

[0040] The raw material mixture is subjected to firing under a reducing atmosphere. In this case, the raw material mixture may be fired as it is, or, if the raw material mixture contains a solvent, the raw material mixture may be fired after removing the solvent.

[0041] The reducing atmosphere is not particularly limited, and examples thereof include a hydrogen (H2) atmosphere, a carbon monoxide (CO) atmosphere, a nitrogen (N2) atmosphere, a mixed gas atmosphere of hydrogen and carbon monoxide and / or nitrogen, a mixed gas atmosphere of hydrogen and an inert gas, and an ammonia (NH3) atmosphere. Of these, a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and nitrogen is preferred because it allows efficient production of the titanium suboxide support. Therefore, a particularly preferred step (1) is a step of calcining a dry mixture containing rutile titanium oxide (preferably, as described above, rutile titanium oxide having a specific surface area within a predetermined range) and a reduction assistant as raw materials under a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and nitrogen.

[0042] The firing may be carried out once or twice or more. When the firing is carried out twice or more, each step is preferably carried out in a reducing atmosphere (preferably a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and nitrogen).

[0043] The firing temperature depends on the conditions of the reducing atmosphere such as the hydrogen concentration, but is preferably, for example, 500°C to 1100°C. This makes it possible to achieve both a high specific surface area and high electrical conductivity in the obtained electrode material. The lower limit of the firing temperature is more preferably 600°C or higher, and even more preferably 650°C or higher, and the upper limit is more preferably 1050°C or lower, and even more preferably 1000°C or lower. In this specification, the firing temperature means the maximum temperature reached in the firing step.

[0044] The calcination time, i.e., the retention time at the calcination temperature, also depends on the conditions of the reducing atmosphere such as the hydrogen concentration, but is preferably, for example, 5 minutes to 100 hours. If the calcination time is within this range, the reaction proceeds more sufficiently, and the productivity of the titanium suboxide support is excellent. It is more preferably 30 minutes to 24 hours, even more preferably 60 minutes to 20 hours, and particularly preferably 2 to 15 hours. When the temperature is lowered after the calcination is completed, a gas other than hydrogen (e.g., nitrogen gas) may be mixed or replaced.

[0045] 2) Process (2) Step (2) is a step of supporting Pt and / or its oxide, and at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide on the titanium suboxide support obtained in step (1). After the above step (1) and before step (2), one or more other steps such as pulverization, water washing, classification, etc. may be included as necessary. The other steps are not particularly limited.

[0046] In step (2), the loading of Pt and / or its oxide and the loading of at least one precious metal selected from Ir, Ru, Rh and Pd and / or its oxide may be performed in any order. Alternatively, Pt and its oxide and the loading of at least one precious metal selected from Ir, Ru, Rh and Pd and / or its oxide may be simultaneously performed. In the following, as one example of a method for producing an electrode material of the present invention, a production method in which Pt and / or an oxide thereof is first supported on the titanium suboxide support obtained in step (1), and then at least one precious metal selected from Ir, Ru, Rh, and Pd and / or an oxide thereof is supported thereon will be described. The step of supporting Pt and / or an oxide thereof will be referred to as step (2-1), and the step of supporting at least one precious metal selected from Ir, Ru, Rh, and Pd and / or an oxide thereof after step (2-1) will be referred to as step (2-2).

[0047] In the above step (2-1), the method for supporting Pt and / or an oxide thereof is not particularly limited as long as Pt and / or an oxide thereof is supported on the titanium suboxide support obtained in step (1). However, it is preferable that the step (2-1) is a step of supporting Pt and / or an oxide thereof using a slurry containing the titanium suboxide support obtained in step (1), Pt and / or a water-soluble compound thereof (hereinafter also collectively referred to as a Pt compound), and a solvent. As for the above step (2-2), there are no particular limitations on the method of loading, so long as at least one precious metal selected from Ir, Ru, Rh and Pd and / or an oxide thereof is loaded on the titanium suboxide support carrying Pt and / or an oxide thereof obtained in step (2-1). However, a preferred method is to load at least one precious metal selected from Ir, Ru, Rh and Pd and / or an oxide thereof using a slurry containing the titanium suboxide support carrying Pt and / or an oxide thereof obtained in step (2-1), at least one precious metal selected from Ir, Ru, Rh and Pd and / or a water-soluble compound thereof (hereinafter also collectively referred to as a second precious metal compound), and a solvent.

[0048] The slurry in the above step (2-1) contains the titanium suboxide support obtained in the above step (1) and a Pt compound, and this slurry is preferably obtained, for example, by mixing the titanium suboxide support obtained in the above step (1) (or a slurry containing the titanium suboxide support) with a solution of a Pt compound. By using this slurry, Pt and / or its oxide can be supported in a more highly dispersed state. The slurry in step (2-2) is also preferably obtained by mixing the titanium suboxide support carrying Pt and / or its oxide (or the slurry containing the titanium suboxide support carrying Pt and / or its oxide) obtained in step (2-1) with a solution of a second precious metal compound. By using this slurry, at least one precious metal selected from Ir, Ru, Rh, and Pd and / or its oxide can be supported in a more highly dispersed state. The slurry may contain one or more of each of the components.

[0049] The method for obtaining the slurry in the above step (2-1) or step (2-2), i.e., the method for mixing the above components, is not particularly limited, but an example thereof includes a method in which a solution of a Pt compound (or a second precious metal compound) is added to a titanium suboxide support (or a titanium suboxide support carrying Pt and / or its oxide) and a solvent are stirred in a vessel, and then the solution is stirred and mixed. The temperature during addition is preferably 40° C. or lower, and it is preferable to heat the mixture to a predetermined temperature (preferably 60 to 100° C., more preferably 70 to 100° C.) while stirring and mixing. The mixture may be stirred with a stirrer using a stirring bar, or a stirrer equipped with a stirring blade such as a propeller type or a paddle type may be used.

[0050] The solvent is not particularly limited, and examples thereof include water, acidic solvents, organic solvents, and mixtures thereof. Examples of organic solvents include alcohol, acetone, dimethylsulfoxide, dimethylformamide, tetrahydrofuran, dioxane, etc., and examples of alcohol include monohydric water-soluble alcohols such as methanol, ethanol, and propanol; dihydric or higher water-soluble alcohols such as ethylene glycol and glycerin; etc. The solvent is preferably water, and more preferably ion-exchanged water.

[0051] The content of the solvent is not particularly limited, but is preferably 1 to 1,000 by weight based on the solid content (total solid content when two or more types are used) of the titanium suboxide support obtained in step (1) (or the titanium suboxide support carrying Pt and / or an oxide thereof obtained in step (2-1)). This makes it possible to more easily obtain an electrode material. The content is more preferably 5 to 500, and even more preferably 10 to 300.

[0052] The slurry in the above steps (2-1) and (2-2) may also contain additives such as acids, alkalis, chelating compounds, organic dispersants, polymeric dispersants, etc. The inclusion of these additives is expected to improve the dispersibility of the titanium suboxide support (or the titanium suboxide support carrying Pt and / or its oxide) contained in the slurry.

[0053] The above-mentioned Pt compound solution or the second precious metal compound solution is not particularly limited as long as it is a solution containing a Pt compound or a second precious metal compound, and examples thereof include inorganic salts such as sulfates, nitrates, chlorides, and phosphates of Pt or the second precious metal; organic acid salts such as acetates and oxalates of Pt or the second precious metal; and nano-sized dispersion solutions of Pt or the second precious metal. Among these, chloride solutions, nitrate solutions, dinitrodiammine nitrate solutions, bis(acetylacetonato)platinum(II) solutions, and the like are preferred. Among these, an aqueous chloride solution is the most preferred from the viewpoint of reactivity.

[0054] The amount of the Pt solution used in the step (2-1) is not particularly limited, but is preferably 0.01 to 0.5 by weight, calculated as Pt element, relative to the total amount of solids in the titanium suboxide support. This allows Pt and / or its oxide to be dispersed more finely. It is more preferably 0.01 to 0.4, and even more preferably 0.01 to 0.3.

[0055] The amount of the second precious metal solution used in the above step (2-2) is also the same, and for example, the weight ratio of the second precious metal, calculated as the elemental amount, to the total solid content of the titanium suboxide support carrying Pt and / or its oxide is preferably 0.01 to 0.5. This allows the second precious metal and / or its oxide to be dispersed more finely. The weight ratio is more preferably 0.01 to 0.4, and even more preferably 0.01 to 0.3.

[0056] In step (2-1) or step (2-2), the mixed solution may be subjected to reduction and / or neutralization as necessary. For example, when reduction is performed, it is preferable to add a reducing agent to the mixed solution to appropriately reduce the Pt compound and the second precious metal compound. When neutralization is performed, it is preferable to add a basic solution to the mixed solution. When performing two or more treatments among reduction, surface treatment, and neutralization, the reducing agent, surfactant, and basic solution may be added separately in any order, or may be added all at once.

[0057] The reducing agent is not particularly limited, but examples thereof include hydrazine chloride, hydrazine, sodium borohydride, alcohol, hydrogen, sodium thiosulfate, citric acid, sodium citrate, L-ascorbic acid, formaldehyde, ethylene, carbon monoxide, etc., and is preferably hydrazine chloride. The amount of the reducing agent added is not particularly limited, but is preferably 0.1 to 2 times the molar equivalent of Pt and the second precious metal contained in the mixed solution.

[0058] The basic solution is not particularly limited, but examples thereof include an aqueous NaOH solution, an aqueous NH3 solution, an aqueous sodium carbonate solution, etc., and is preferably an aqueous NaOH solution. The neutralization temperature in the neutralization step is preferably 60°C to 100°C, more preferably 70°C to 100°C.

[0059] In the above steps (2-1) and (2-2), it is preferable to remove moisture and by-products (also called by-products) from the above mixed liquid (which may have been subjected to reduction treatment and / or neutralization treatment as necessary, as described above). The means for removing them is not particularly limited, but it is preferable to remove moisture and by-products by, for example, filtration, washing with water, drying, evaporation under heating, or the like. Here, it is preferable to remove the by-products by washing with water. If by-products remain in the electrode material, they may dissolve into the system during operation of the polymer electrolyte fuel cell, which may cause deterioration of the power generation characteristics or damage to the system. The method of washing with water is not particularly limited as long as it can remove water-soluble substances not supported on the titanium suboxide carrier from the system, and examples of the method include filtration, washing with water, decantation, etc. At this time, it is preferable to remove the by-products by washing with water until the electrical conductivity of the washing water is 30 μS / cm or less. It is more preferable to wash with water until the electrical conductivity is 10 μS / cm or less.

[0060] In the above step (2-1) or step (2-2), it is more preferable to remove moisture and by-products from the mixed liquid and then calcinate the powder. This allows Pt, the second precious metal, or its oxide, which has a low degree of crystallinity and is difficult to express electrochemical properties, to have a degree of crystallinity suitable for expressing electrochemical properties. The degree of crystallinity may be such that a peak derived from Pt, the second precious metal, their alloy, or their oxide can be confirmed in XRD. When calcining the dried powder, it is preferable to calcinate under a reducing atmosphere. The reducing atmosphere is as described above, and a hydrogen atmosphere is particularly preferable. The calcination temperature is not particularly limited, but is preferably, for example, 500 to 1000°C. The calcination time is also not particularly limited, but is preferably, for example, 30 minutes to 24 hours. This allows Pt, the second precious metal, or its oxide to be bonded to the titanium suboxide support in a state suitable for expressing electrochemical properties. A favorable bonding state can be confirmed by a peak derived from Pt or the second precious metal or its oxide being shifted to a higher or lower angle side in XRD, compared to the case where firing is not performed in a reducing atmosphere, and preferably shifted to a higher angle side.

[0061] The particularly preferred step (2-1) is a step of reducing the mixed liquid containing the titanium suboxide support and the Pt compound obtained in the step (1) above, filtering, drying, and calcining the resulting powder. Similarly, the above step (2-2) is particularly preferably a step of reducing the mixed liquid containing the titanium suboxide support carrying Pt and / or an oxide thereof and the second precious metal compound obtained in step (2-1), filtering, drying, and calcining the obtained powder.

[0062] In the above, a case has been described in which Pt and / or an oxide thereof is first supported on the titanium suboxide support obtained in step (1), and then at least one precious metal selected from Ir, Ru, Rh, and Pd and / or an oxide thereof is supported thereon. However, when the order of the supporting is reversed, the order of the above steps (2-1) and (2-2) can be reversed, and when these supporting operations are carried out simultaneously, the steps (2-1) and (2-2) can be carried out together.

[0063] 3. Electrodes, fuel cells, or water electrolysis cells The electrode material of the present invention can form an electrode having high resistance to high potential and excellent conductivity, and therefore can be suitably used as an electrode material for fuel cells, solar cells, transistors, liquid crystal displays, etc. In particular, the electrode material can be suitably used as an electrode for polymer electrolyte fuel cells (PEFCs) or water electrolysis cells. Such an electrode constructed using the electrode material of the present invention and a fuel cell including such an electrode also constitute part of the present invention, and a water electrolysis cell constructed using the electrode material of the present invention also constitutes part of the present invention. EXAMPLES

[0064] In order to explain the present invention in detail, specific examples are given below, but the present invention is not limited to these examples. Unless otherwise specified, "%" means "% by weight (% by mass)".

[0065] Example 1 (1) Preparation of titanium suboxide support Rutile-type titanium dioxide (manufactured by Sakai Chemical Industry Co., Ltd., product name "STR-100N", specific surface area 100 m 2 The mixture was dry-mixed with 15.8 g of titanium suboxide (100 vol.% hydrogen) at 400 ml / min in an atmospheric firing furnace and heated to 710°C over 68 minutes. The mixture was then held at 710°C for 8 hours and then naturally cooled to room temperature while passing 5 vol.% hydrogen / nitrogen at 400 ml / min. The mixture was then heated to 900°C over 87 minutes and held at 900°C for 3 hours. The mixture was then naturally cooled to room temperature to obtain titanium suboxide support 1. (2) Preparation of Pt-loaded titanium suboxide powder 7.0 g of the obtained titanium suboxide support 1 and 778 g of ion-exchanged water were weighed into a beaker and mixed with stirring to obtain a titanium suboxide support slurry 1. In a separate beaker, 5.2 g of a chloroplatinic acid aqueous solution (15.343% as Pt, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) was diluted with 31.3 g of ion-exchanged water, and then 0.2 g of hydrazine chloride (manufactured by Tokyo Kasei Kogyo Co., Ltd., product name "Hydrazine Dihydrochloride") was added and mixed with stirring to prepare a mixture (this is referred to as "mixed Pt aqueous solution 1"). While stirring the titanium suboxide support slurry 1, 36.7 g of the mixed Pt aqueous solution 1 prepared in another beaker was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70° C. Furthermore, 31 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and kept at a liquid temperature of 70° C. for 1 hour, and then filtered, washed with water, and dried according to a conventional method to evaporate all water, and 6.3 g of powder was obtained. The obtained powder 6.0 g was placed in an alumina boat, and while 100 vol% hydrogen was passed through it at 400 ml / min in an atmospheric firing furnace, the temperature was raised to 900° C. over 87 minutes, and the mixture was kept at 900° C. for 3 hours, and then naturally cooled to room temperature to obtain Pt-supported titanium suboxide powder 1. (3) Preparation of IrPt-supported titanium suboxide powder 5.2 g of the obtained Pt-supported titanium suboxide powder 1 and 480 g of ion-exchanged water were weighed into a beaker and mixed with stirring to obtain Pt-supported titanium suboxide slurry 1. In a separate beaker, 0.2 g of hydrazine chloride (manufactured by Tokyo Chemical Industry Co., Ltd., product name "Hydrazine Dihydrochloride") was added to 5.2 g of iridium chloride hydrochloride aqueous solution (8.604% as Ir, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) and mixed with stirring to prepare a mixture (this is referred to as "mixed Ir aqueous solution 1"). While stirring the Pt-supported titanium suboxide slurry 1, 5.4 g of the above mixed Ir aqueous solution 1 prepared in another beaker was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70 ° C. Furthermore, 19 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and kept at a liquid temperature of 70 ° C. for 1 hour, and then filtered, washed with water, and dried according to a conventional method to evaporate all water, and 4.7 g of powder was obtained. The obtained powder was placed in a 2.0 g alumina boat, and heated to 900 ° C. over 87 minutes while circulating 100 vol% hydrogen at 400 ml / min in an atmospheric firing furnace, and kept at 900 ° C. for 3 hours, and then naturally cooled to room temperature to obtain IrPt-supported titanium suboxide powder 1. (4) Fabrication of membrane electrode assembly 0.2 g of the obtained IrPt-supported titanium suboxide powder 1, 168 μl of 20 wt % Nafion solution (Sigma-Aldrich), 120 μl of t-butyl alcohol (Wako Pure Chemical Industries, Ltd.), 24 μl of ion-exchanged water, and 1.4 g of 2 mmφZrO2 beads were placed in a screw tube and dispersed for 150 minutes using an ultrasonic cleaner to obtain IrPt-supported titanium suboxide ink 1. 40 μl of the obtained IrPt-supported titanium suboxide ink 1 was dropped onto a Teflon (registered trademark) sheet, coated using a bar coater with a groove depth of 10 μm, and then naturally dried to obtain an IrPt-supported titanium suboxide sheet 1. 0.02 g of commercially available 50 wt% Pt-loaded carbon (manufactured by NE Chemcat), 61 μl of 20 wt% Nafion solution (manufactured by Sigma-Aldrich), 179 μl of t-butyl alcohol (manufactured by Wako Pure Chemical Industries, Ltd.), 89 μl of ion-exchanged water, and 1.6 g of 2 mmφ ZrO2 beads were placed in a screw tube and dispersed for 150 minutes using an ultrasonic cleaner to obtain Pt-loaded carbon ink 1. 40 μl of the obtained Pt-supported carbon ink 1 was dropped onto a Teflon (registered trademark) sheet, coated using a bar coater with a groove depth of 100 μm, and then naturally dried to obtain a Pt-supported carbon sheet 1. An electrolyte membrane (manufactured by DuPont, product name NR-212) was cut to 3 cm x 3 cm, and then an IrPt-supported titanium suboxide sheet 1 and a Pt-supported carbon sheet 1 were each cut to 1 cm x 1 cm. The IrPt-supported titanium suboxide sheet 1, electrolyte membrane, and Pt-supported carbon sheet 1 were stacked in this order and hot-pressed at 140°C for 6 minutes with a set pressure of 1 MPa using a heated hydraulic press (manufactured by Toyo Seiki Seisakusho, product name Mini Test Press MP-WNH). Thereafter, the Teflon (registered trademark) sheet was peeled off from the IrPt-supporting titanium suboxide sheet 1 and the Pt-supporting carbon sheet 1 to obtain a membrane electrode assembly 1.

[0066] Example 2 (1) Preparation of titanium suboxide support Rutile-type titanium dioxide (manufactured by Sakai Chemical Industry Co., Ltd., product name "STR-100N", specific surface area 100 m 2 15.8 g of titanium suboxide (100 / g) and 4.2 g of titanium hydride (manufactured by Toho Tech Co., Ltd., product name "titanium hydride powder TCH-450") were dry-mixed, then placed in an alumina boat and heated to 710°C over 68 minutes in an atmospheric firing furnace while 100 vol% hydrogen was passed through at 400 ml / min. After holding at 710°C for 8 hours, the mixture was naturally cooled to room temperature while 5 vol% hydrogen / nitrogen was passed through at 400 ml / min. Thereafter, the mixture was heated to 1000°C over 87 minutes, held at 1000°C for 6 hours, and naturally cooled to room temperature to obtain titanium suboxide support 2. (2) Preparation of Pt-loaded titanium suboxide powder 7.0 g of the obtained titanium suboxide support 2 and 778 g of ion-exchanged water were weighed into a beaker and mixed with stirring to obtain a titanium suboxide support slurry 2. In a separate beaker, 5.2 g of a chloroplatinic acid aqueous solution (15.343% as Pt, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) was diluted with 31.3 g of ion-exchanged water, and then 0.2 g of hydrazine chloride (manufactured by Tokyo Kasei Kogyo Co., Ltd., product name "Hydrazine Dihydrochloride") was added and mixed with stirring to prepare a mixture (this is referred to as "mixed Pt aqueous solution 2"). While stirring the titanium suboxide support slurry 2, 18.4 g of the mixed Pt aqueous solution 2 was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70° C. Furthermore, 15.5 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and kept at a liquid temperature of 70° C. for 1 hour, and then filtered, washed with water, and dried in a conventional manner to evaporate all water, obtaining 6.3 g of powder. The obtained powder was placed in a 6.0 g alumina boat, and heated to 900° C. over 87 minutes in an atmospheric firing furnace while circulating 100 vol% hydrogen at 400 ml / min, and then kept at 900° C. for 3 hours, and then naturally cooled to room temperature to obtain Pt-supported titanium suboxide powder 2. (3) Preparation of IrPt-supported titanium suboxide powder 5.2 g of the obtained Pt-supported titanium suboxide powder 2 and 480 g of ion-exchanged water were weighed into a beaker and mixed by stirring to obtain Pt-supported titanium suboxide slurry 2. In a separate beaker, 0.2 g of hydrazine chloride (manufactured by Tokyo Chemical Industry Co., Ltd., product name "Hydrazine Dihydrochloride") was added to 5.2 g of iridium chloride hydrochloride aqueous solution (8.604% as Ir, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) and mixed by stirring to prepare a mixture (this is referred to as "mixed Ir aqueous solution 2"). While stirring the Pt-supported titanium suboxide slurry 2, 5.4 g of the above mixed Ir aqueous solution 2 prepared in another beaker was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70 ° C. Furthermore, 19 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and kept at a liquid temperature of 70 ° C. for 1 hour, and then filtered, washed with water, and dried according to a conventional method to evaporate all water, and 4.7 g of powder was obtained. The obtained powder was placed in a 2.0 g alumina boat, and while 100 vol% hydrogen was passed through it at 400 ml / min in an atmospheric firing furnace, the temperature was raised to 900 ° C. over 87 minutes, and the mixture was kept at 900 ° C. for 3 hours, and then naturally cooled to room temperature to obtain IrPt-supported titanium suboxide powder 2. Thereafter, the same procedure as in Example 1 was carried out to obtain a membrane / electrode assembly 2.

[0067] Example 3 The same procedures as in Example 2 were carried out, except that the holding time at 1000°C in "(1) Production of titanium suboxide support" in Example 2 was changed from 6 hours to 3 hours to obtain a titanium suboxide support 3, and the amount of mixed Ir aqueous solution 2 added to Pt-supported titanium suboxide slurry 2 in "(3) Preparation of IrPt-supported titanium suboxide powder" and the amount of 1.0 N sodium hydroxide aqueous solution were halved, to obtain an IrPt-supported titanium suboxide powder 3. Furthermore, a membrane electrode assembly 3 was obtained in the same manner as in Example 1 using the obtained IrPt-supported titanium suboxide powder 3.

[0068] Example 4 The same procedure as in Example 2 was carried out to obtain IrPt-supported titanium suboxide powder 4, except that the contents of "(2) Preparation of Pt-supported titanium suboxide powder" and "(3) Preparation of IrPt-supported titanium suboxide powder" in Example 2 were changed as follows. In addition, a membrane electrode assembly 4 was obtained in the same manner as in Example 1 using the obtained IrPt-supported titanium suboxide powder 4. (2) Preparation of Pt-loaded titanium suboxide powder 7.0 g of the obtained titanium suboxide support 2 and 778 g of ion-exchanged water were weighed into a beaker and mixed with stirring to obtain a titanium suboxide support slurry 2. In a separate beaker, 5.2 g of a chloroplatinic acid aqueous solution (15.343% as Pt, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) was diluted with 31.3 g of ion-exchanged water, and then 0.2 g of hydrazine chloride (manufactured by Tokyo Kasei Kogyo Co., Ltd., product name "Hydrazine Dihydrochloride") was added and mixed with stirring to prepare a mixture (this is referred to as "mixed Pt aqueous solution 4"). While stirring the titanium suboxide support slurry 2, 36.7 g of the mixed Pt aqueous solution 4 was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70° C. Furthermore, 31 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and kept at a liquid temperature of 70° C. for 1 hour, and then filtered, washed with water, and dried in a conventional manner to evaporate all water, obtaining 6.3 g of powder. The obtained powder was placed in an alumina boat of 6.0 g, and heated to 900° C. over 87 minutes in an atmospheric firing furnace while circulating 100 vol% hydrogen at 400 ml / min, and then kept at 900° C. for 3 hours, and then naturally cooled to room temperature to obtain Pt-supported titanium suboxide powder 4. (3) Preparation of IrPt-supported titanium suboxide powder 3.0 g of the obtained Pt-supported titanium suboxide powder 4 and 530 g of ion-exchanged water were weighed into a beaker and stirred and mixed to obtain Pt-supported titanium suboxide slurry 4. In a separate beaker, 0.1 g of hydrazine chloride (manufactured by Tokyo Chemical Industry Co., Ltd., product name "Hydrazine Dihydrochloride") was added to 3.3 g of iridium chloride hydrochloride aqueous solution (8.604% as Ir, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) and stirred and mixed to prepare a solution (this is referred to as "mixed Ir aqueous solution 4"). While stirring the Pt-supported titanium suboxide slurry 4, 3.4 g of the above mixed Ir aqueous solution prepared in another beaker was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70° C. Furthermore, 12 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and held at a liquid temperature of 70° C. for 1 hour, and then filtered, washed with water, and dried according to a conventional method to evaporate all water, thereby obtaining 2.2 g of powder 4. 2.0 g of the obtained powder 4 was placed in an alumina boat, and while 100 vol% hydrogen was passed through it at 400 ml / min in an atmospheric firing furnace, the temperature was raised to 1000° C. over 97 minutes, and the mixture was held at 1000° C. for 3 hours, and then naturally cooled to room temperature to obtain IrPt-supported titanium suboxide powder 4. Thereafter, the same procedure as in Example 1 was carried out to obtain a membrane / electrode assembly 4.

[0069] Example 5 The same procedure as in Example 4 was carried out, except that the content of "(3) Preparation of IrPt-supported titanium suboxide powder" in Example 4 was changed to the content of "(3) Preparation of RuPt-supported titanium suboxide powder" below, to obtain RuPt-supported titanium suboxide powder 5. Furthermore, a membrane electrode assembly 5 was obtained in the same manner as in Example 1 using the obtained RuPt-supported titanium suboxide powder 5. (3) Preparation of RuPt-supported titanium suboxide powder 1.5 g of the obtained Pt-supported titanium suboxide powder 4 and 260 g of ion-exchanged water were weighed into a beaker and mixed by stirring to obtain Pt-supported titanium suboxide slurry 5. In a separate beaker, 0.1 g of hydrazine chloride (manufactured by Tokyo Chemical Industry Co., Ltd., product name "Hydrazine Dihydrochloride") was added to 1.28 g of a ruthenium chloride aqueous solution (8.455% as Ru, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) and mixed by stirring to prepare a solution (this is referred to as "mixed Ru aqueous solution 5"). While stirring the Pt-supported titanium suboxide slurry 5, 1.38 g of the above mixed Ru aqueous solution prepared in another beaker was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70 ° C. Furthermore, 6 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and kept at a liquid temperature of 70 ° C. for 1 hour, and then filtered, washed with water, and dried according to a conventional method to evaporate all water, and 1.3 g of powder was obtained. The obtained powder was placed in a 1.0 g alumina boat, and while 100 vol% hydrogen was passed through it at 400 ml / min in an atmospheric firing furnace, the temperature was raised to 900 ° C. over 87 minutes, and the mixture was kept at 900 ° C. for 3 hours, and then naturally cooled to room temperature to obtain RuPt-supported titanium suboxide powder 5. Thereafter, the same procedure as in Example 1 was carried out to obtain a membrane / electrode assembly 5.

[0070] Example 6 The same procedure as in Example 3 was carried out to obtain an IrPt-supported titanium suboxide powder, except that the amount of the mixed Pt aqueous solution 2 and the amount of the 1.0 N sodium hydroxide aqueous solution added to the titanium suboxide support slurry 2 in "(2) Preparation of Pt-supported titanium suboxide powder" in Example 3 were tripled, and the amount of the mixed Ir aqueous solution 2 and the amount of the 1.0 N sodium hydroxide aqueous solution added to the Pt-supported titanium suboxide slurry 2 in "(3) Preparation of IrPt-supported titanium suboxide powder" were quadrupled. Furthermore, the obtained IrPt-supported titanium suboxide powder was used instead of the Pt-supported titanium suboxide powder 4 in Example 5, and the amount of the mixed Ru aqueous solution and the amount of the 1.0 N sodium hydroxide aqueous solution added to the IrPt-supported titanium suboxide slurry were halved, and the same procedure as in Example 5 was carried out to obtain an RuIrPt-supported titanium suboxide powder. Thereafter, the same procedure as in Example 1 was carried out to obtain a membrane electrode assembly 6.

[0071] Comparative Example 1 The Pt-supported titanium suboxide powder 1 obtained in Example 1 “(2) Preparation of Pt-supported titanium suboxide powder” was used as comparative powder 1, and a comparative membrane electrode assembly 1 was obtained in the same manner as in Example 1 (4) “Preparation of membrane electrode assembly”.

[0072] Comparative Example 2 The procedure of Example 1 was repeated except that "(2) Preparation of Pt-supported titanium suboxide powder" in Example 1 was changed as follows, and "(3) Preparation of IrPt-supported titanium suboxide powder" was not performed, to obtain comparative powder 2. Comparative membrane electrode assembly 2 was also obtained in the same manner as in Example 1 using the obtained comparative powder 2. (2) Preparation of Pt-loaded titanium suboxide powder 7.8 g of the obtained titanium suboxide carrier and 980 g of ion-exchanged water were weighed into a beaker and mixed with stirring to obtain a titanium suboxide carrier slurry. In a separate beaker, 12.7 g of a chloroplatinic acid aqueous solution (15.343% as platinum, manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) was diluted with 76.4 g of ion-exchanged water, and then 0.5 g of hydrazine chloride (manufactured by Tokyo Kasei Kogyo Co., Ltd., product name "Hydrazine Dihydrochloride") was added and mixed with stirring to prepare a solution (this is referred to as a "mixed aqueous solution"). While stirring the titanium suboxide carrier slurry, 89.6 g of the above mixed aqueous solution was added, and then the mixture was stirred and mixed while being heated to a liquid temperature of 70° C. Furthermore, 76 g of 1.0 N sodium hydroxide aqueous solution was added and stirred and mixed, and the mixture was heated and kept at a liquid temperature of 70° C. for 1 hour, and then filtered, washed with water, and dried in a conventional manner to evaporate all water, obtaining 7.0 g of powder. The obtained powder was placed in a 4.0 g alumina boat, and heated to 900° C. over 87 minutes in an atmospheric firing furnace while circulating 100 vol% hydrogen at 400 ml / min, and then kept at 900° C. for 3 hours, and then naturally cooled to room temperature to obtain comparative powder 2.

[0073] Comparative Example 3 Comparative powder 1 of Pt-supported titanium suboxide obtained in Comparative Example 1 and powder of Ir-supported titanium suboxide in which Ir was supported by the method described in "(3) Preparation of IrPt-supported titanium suboxide powder" and the titanium suboxide support obtained in "(1) Preparation of titanium suboxide support" described in Example 1 were physically mixed in a weight ratio of 55:45 to obtain comparative powder 3. Furthermore, a comparative membrane electrode assembly 3 was obtained in the same manner as in Example 1 using the obtained comparative powder 3.

[0074] Comparative Example 4 Comparative powder 4 of Ir-supported titanium suboxide was obtained by supporting Ir on the titanium suboxide support obtained in "(1) Preparation of titanium suboxide support" of Comparative Example 1 using the method described in "(3) Preparation of IrPt-supported titanium suboxide powder" in Example 1. Furthermore, comparative membrane electrode assembly 4 was obtained in the same manner as in Example 1 using the obtained comparative powder 4.

[0075] Comparative Example 5 The same procedure as in Comparative Example 1 was carried out except that the heating temperature in "(2) Preparation of Pt-supported titanium suboxide powder" was changed from 900°C to 1000°C, and the Pt-supported titanium suboxide powder thus obtained was physically mixed with iridium black (manufactured by Alfa Aesar) in a weight ratio of 88:12 to obtain Comparative Powder 5. Furthermore, using the obtained Comparative Powder 5, Comparative Membrane Electrode Assembly 5 was obtained in the same manner as in Example 1.

[0076] Comparative Example 6 (1) Preparation of titanium suboxide support Anatase-type titanium dioxide (manufactured by Sakai Chemical Industry Co., Ltd., product name "CS-41L", specific surface area 50 m 2 40.0 g of titanium hydride (10.0 g / g) and 10.0 g of titanium hydride (manufactured by Toho Tech Co., Ltd., product name "titanium hydride powder TCH-450") were dry-mixed, then placed in an alumina boat and heated to 800°C over 77 minutes in an atmospheric firing furnace while 100 vol% hydrogen was passed through at 400 ml / min. The mixture was then held at 800°C for 8 hours and then naturally cooled to room temperature to obtain a titanium suboxide support. (2) Preparation of Pt-loaded titanium suboxide powder 2.0 g of the obtained titanium oxide carrier and 480 g of ion-exchanged water were weighed into a beaker and stirred and mixed to obtain a titanium oxide carrier slurry. In another beaker, 6.4 g of an aqueous solution of chloroplatinic acid (15.343% as platinum, manufactured by Tanaka Precious Metals Industry Co., Ltd.) was diluted with 38.6 g of ion-exchanged water, and then 0.3 g of hydrazine chloride (manufactured by Tokyo Chemical Industry Co., Ltd., trade name "Hydrazine Dihydrochloride") was added and stirred and mixed (this is referred to as the "mixed aqueous solution"). While stirring the titanium oxide carrier slurry, 45.3 g of the above-mentioned mixed aqueous solution prepared in another beaker was added, and then stirred and mixed while heating and maintaining the liquid temperature at 70°C. Further, 38 g of 1.0 N aqueous sodium hydroxide solution was added and stirred and mixed, and after heating and maintaining the liquid temperature at 70°C for 1 hour, filtration, washing with water, and drying were carried out according to the conventional method to evaporate all the moisture, and 1.8 g of powder was obtained. 1.5 g of the obtained powder was placed in an alumina boat, and while flowing 100 vol% hydrogen at 400 ml / min in an atmospheric firing furnace, the temperature was raised to 800°C over 77 minutes, held at 800°C for 3 hours, and then naturally cooled to room temperature to obtain Comparative Powder 6. Also, using the obtained Comparative Powder 6, a Comparative Membrane Electrode Assembly 6 was obtained in the same manner as in Example 1.

[0077] Various Measurements Regarding the powders obtained in Examples 1 to 6 and Comparative Examples 1 to 6, the following various measurements were carried out. The X-ray diffraction patterns are shown in FIGS. 1 to 3 and FIGS. 14 to 20, and the electron micrographs are shown in FIGS. 4 to 13. The results of other various measurements are shown in Table 1. <Specific Surface Area (BET-SSA)> According to the provisions of JIS Z8830 (2013), after heat-treating the sample in a nitrogen atmosphere at 200°C for 60 minutes, the specific surface area (BET-SSA) was measured using a specific surface area measuring device (manufactured by Mountech Co., Ltd., trade name "Macsorb HM-1220"). <Pt Loading, Ir Loading, Ru Loading> Using a scanning fluorescent X-ray analyzer ZSX PrimusII (manufactured by Rigaku Corporation), the Pt content and Ir content in the sample were measured, and the Pt loading, Ir loading, and Ru loading were calculated. <Average primary particle diameter of supported Pt, Ir, and Ru> First, in a transmission electron microscope photograph (also referred to as a TEM image or TEM photograph), the major axis and minor axis of Pt, Ir, and Ru particles were measured using a ruler or the like, and the primary particle diameter was determined by dividing the average value of the major axis and minor axis by the magnification of the photograph. Further, 80 Pt, Ir, and Ru particles were randomly extracted from the TEM image, the primary particle diameter of all the particles was measured by the above method, the maximum value among the measured values was defined as the maximum primary particle diameter, the minimum value among the measured values was defined as the minimum primary particle diameter, and the average primary particle diameter was determined by averaging the measured values. Note that the magnification of the TEM image may be any magnification, but the preferred range is from 20,000 times to 500,000 times. Since Pt, Ir, and Ru cannot be distinguished from each other in the TEM image, they were measured as the average particle diameter of all the noble metals.

[0078] <Observation with an electron microscope photograph> Observation was carried out using a field emission transmission electron microscope JEM-2100F (manufactured by JEOL Ltd.). <X-ray diffraction pattern (XRD measurement)> Under the following conditions, a powder X-ray diffraction pattern was measured using an X-ray diffractometer (manufactured by Rigaku Corporation, trade name "RINT-TTR3"). X-ray source: Cu-Kα ray Measurement range: 2θ = 10 to 70° Scan speed: 5° / min Voltage: 50 kV Current: 300 mA

[0079] <Volume resistivity (also referred to as volume specific resistance)> For the measurement of the volume resistivity of the powder, a powder resistivity measurement system MCP-PD51 type manufactured by Mitsubishi Chemical Analytech Co., Ltd. was used. The powder resistivity measurement system is composed of a powder press section by hydraulic pressure, a four-probe probe, and a high-resistance measurement device (Loresta-GX MCP-T700 manufactured by the same company). According to the following procedure, the value of the volume resistivity (Ω·cm) was determined. 1) Put the sample powder into a press jig (diameter 20 mm) equipped with a four-point probe on the bottom and set it in the pressurizing part of the powder resistance measurement system. Connect the probe and the high resistance measurement device with a cable. 2) Apply pressure up to 20 kN using a hand press. Measure the powder thickness with a digital caliper and the resistance value with a high resistance measuring device. 3) Calculate the volume resistivity (Ω cm) from the base area, thickness, and resistance value of the powder using the following formula.

[0080]

number

[0081] <Surface resistivity measurement> The surface resistivity of the sheet was measured using a powder resistivity measurement system, Model MCP-PD51, manufactured by Mitsubishi Chemical Analytech Co., Ltd. The sheet was cut into a piece of 1 cm x 2 cm, and the sample size was set to 1 cm x 2 cm in the powder resistivity measurement system, Model MCP-PD51. A four-point probe was then placed directly on the sheet to determine the surface resistivity (Ω / sq.).

[0082] <Membrane electrode assembly power generation test> The electrode using the powder in the examples and comparative examples was placed on the anode side, with a Pt weight of 0.2 mg Pt / cm 2 The Pt-supported carbon electrode was placed on the cathode side, and the membrane electrode assembly was assembled into a single cell (manufactured by Miklab, electrode area 1cm x 1cm, Au 10μm-plated Cu separator, straight flow path specification). Using a PEFC single cell evaluation device (manufactured by Toyo Corporation), the cell temperature was set to 80°C, the anode side was set to 75°C and humidified 100% H2 500ml / min, and the cathode side was set to 75°C and humidified 100% O2 500ml / min. The open voltage was swept from 0.2V to 1.0A / cm. 2 The voltage and cell resistance at each point were measured. <Membrane electrode assembly durability test 1> After conducting power generation test 1, the open circuit voltage was switched to 0.6 V every 3 seconds, and this was counted as one cycle. This was repeated 1000 times, and the power generation test was conducted again. 2 The voltage at that point was measured. <Membrane electrode assembly durability test 2> After carrying out power generation test 1, the single cell was inverted and the cell temperature was set to 80°C, the anode side was set to 75°C and humidified to 100% H2500ml / min, and the cathode side was set to 75°C and humidified to 100% N2500ml / min. After applying 1.7V for 4 hours, the single cell was inverted and a power generation test was carried out again, with a current of 0.5A / cm 2 The voltage at that point was measured. <Water electrolysis test> The electrode using the powder in the examples and comparative examples was placed on the cathode side, with a Pt weight of 0.2 mg Pt / cm 2 The Pt-supported carbon electrode was placed on the anode side, and the membrane electrode assembly was assembled into a single cell (manufactured by Miklab, electrode area 1cm x 1cm, Au 10μm-plated Cu separator, straight flow path specification). Using a PEFC single cell evaluation device (manufactured by Toyo Corporation), the cell temperature was set to 80°C, the anode side was set to 75°C and humidified with 100% N at 2500ml / min, and the cathode side was set to 75°C and humidified with 100% N at 2500ml / min. The voltage was swept from 1.0V to 2.0V, and the current was measured at 0.1mA / cm. 2 The voltage at that point was measured.

[0083] [Table 1]

[0084] From the XRD measurement results shown in FIGS. 1 to 3, it was confirmed that the titanium suboxide supports used in Examples 1 to 5 had no observed peaks other than those derived from Ti4O7 and Ti3O5. As shown in Table 1, the powders of Examples 1, 2, and 4, in which Pt and Ir are supported on such a titanium suboxide support, and the powder of Example 5, in which Pt and Ru are supported on such a titanium suboxide support, were confirmed to have lower surface resistivity when made into sheets, compared to the powders of Comparative Examples 1 and 2, in which only Pt is supported, and the powder of Comparative Example 4, in which only Ir is supported, and it was considered that oxidation during the electrode formation process was suppressed. Furthermore, the powders of Examples 1, 2, and 4, in which Pt and Ir are supported on a titanium suboxide support, and the powder of Example 5, in which Pt and Ru are supported on a titanium suboxide support, had higher voltages and lower cell resistances when configured into a fuel cell than the powders of Comparative Examples 1 and 2, in which only Pt was supported, the powder of Comparative Example 3, in which Pt-supported titanium suboxide and Ir-supported titanium suboxide were physically mixed, the powder of Comparative Example 4, in which only Ir was supported, and the powder of Comparative Example 5, in which Pt-supported titanium suboxide and iridium black were physically mixed. These facts demonstrate that there is technical significance in supporting Pt and Ir, or Ru, on a titanium suboxide support. Furthermore, the powders of Examples 1, 2, and 4 had higher voltages in a test in which the open circuit voltage was switched between 0.6 V 1,000 times (durability test 1) and in a test in which 1.7 V was applied for 4 hours (durability test 2) than the powder of the comparative example, and it was confirmed that they had excellent durability at normal voltages and durability to high potentials. The powder of Example 3 has a total precious metal loading amount, which is the combined amount of Pt and Ir loaded, that is less than half that of Example 1. However, it has a lower surface resistivity than Comparative Example 1, in which only Pt is loaded and the total precious metal loading amount is slightly greater than that of Example 3. When a fuel cell was formed, the open circuit voltage, the voltage in a test in which 0.6 V was switched 1,000 times (durability test 1), and the voltage in a test in which 1.7 V was applied for 4 hours (durability test 2) were all high, confirming that the powder has excellent durability at both normal voltages and high potentials. Furthermore, the water electrolysis cells constructed using the powders of Examples 1 to 5 were operated at a lower voltage than the water electrolysis cell constructed using the powder of Comparative Example 1 which supported only Pt, confirming that these powders have excellent water electrolysis activity. In addition, a fuel cell anode was prepared in the same manner as in the Examples using a commercially available powder of 50 wt % Pt-supported carbon (manufactured by NE Chemcat Corporation), and the voltage was measured at 1.7 V and 4 hours later at 0.37 V, and a water electrolysis cell anode was prepared and the voltage was measured at 1.56 V. From these results, it was also confirmed that the electrode material of the present invention has superior performance in terms of durability to high potentials and water electrolysis activity compared to carbon-based electrode materials conventionally used as materials for fuel cells and water electrolysis cells.< / tio>

Claims

1. Powder X-ray diffraction reveals that Ti 4 O 7 and / or Ti 3 O 5 On a titanium suboxide support where no peaks other than those due to the Pt, and at least one precious metal selected from Ir and Ru is supported thereon, BET specific surface area is 7m 2 / g or more, 15m 2 / g or less.

2. 2. The electrode material according to claim 1, wherein the at least one precious metal selected from the group consisting of Pt, Ir and Ru has an average primary particle size of 1 to 20 nm.

3. 3. The electrode material according to claim 1, which is an electrode material for a polymer electrolyte fuel cell.

4. An electrode made of the electrode material according to any one of claims 1 to 3.

5. A fuel cell comprising the electrode according to claim 4.

6. A water electrolysis cell comprising the electrode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Electrochemical cell, electrode and electrocatalyst for an electrochemical cell

    DE202015106071U1

  • Electrode carrier material and manufacturing method thereof, electrode material, electrode, and solid polymer fuel cell

    JP2019075305A

  • KR2018-0017861

  • Pump module and evaporated fuel process device

    WO2018096815A1

  • Electrode material and method for producing same

    WO2018096851A1